Use of Granulocyte-colony Stimulating Factor During Chemotherapy and Its Association With CA27.29 and Circulating Tumor Cells-Results From the SUCCESS A Trial - Hepp, Philip; Fasching, Peter; Beckmann, Matthias; Fehm, Tanja; Salmen, Jessica; Hagenbeck, Carsten; Jaeger, Bernadette; Widschwendter, Peter; De Gregorio, Nikolaus; Schochter, Fabienne; Mahner, Sven; Harbeck, Nadia; et al. (Clinical Breast Cancer, 2018)
Little is known about the effect of granulocyte colony-stimulating factor (G-CSF) treatment during adjuvant chemotherapy on prognostic markers. The present study explored the association between G-CSF and changes in cancer antigen (CA)27.29 and circulating tumor cell (CTC) levels during therapy.A total of 3754 node-positive or high-risk node-negative early-stage breast cancer patients were treated within the SUCCESS-A trial (simultaneous study of gemcitabine-docetaxel combination adjuvant treatment, as well as extended bisphosphonate and surveillance-trial). CA27.29 and CTCs were determined before the start and within 6 weeks after the end of chemotherapy.Overall, 1324 of the 2646 patients (50.0%) available for analysis had >= 1 G-CSF applications during chemotherapy. G-CSF application was significantly associated with CA27.29 status before and after chemotherapy (? = 30.6, df = 3; P < .001), because 238 patients (18.0%) with G-CSF treatment but only 146 (11.0%) without G-CSF treatment switched from a negative CA27.29 status before to a positive CA27.29 status after chemotherapy. In addition, patients with G-CSF application showed a significantly greater increase in CA27.29 levels after chemotherapy compared with patients without any G-CSF application during chemotherapy (Mann-Whitney U test; Z = -7.81, P < .001). No significant association was found between G-CSF application and CTC status before or after chemotherapy (? = 1.2, df = 3; P = .75).Cautious interpretation is needed regarding elevated levels of MUC-1-derived tumor markers such as CA27.29 shortly after adjuvant chemotherapy when G-CSF has been given, because G-CSF treatment was associated with increased CA27.29 levels after chemotherapy.
EVALuna2:56150